Analisis determinan sektor industri pengolahan di Indonesia - Samosir, Sanny; Nurjanah, Rahma; Bahri, Zainul (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2023)
The objectives of this study are to: 1) analyze the growth of investments, business units, and workforce in the manufacturing sector's gross domestic product in Indonesia for the period 2000–2021; and 2) evaluate the manufacturing sector's contribution to Indonesia's GDP for the 2000–2021 period. 3) Examine the key variables that have the greatest impact on Indonesia's manufacturing sector's GDP between 2000 and 2021. The average investment, the average number of business units, and the average number of employees in Indonesia's manufacturing industry sector between 2000 and 2021 were 31.39 percent, 2.08 percent, and 0.37 percent, respectively. According to the findings, business units and labor had a significant effect on the gross domestic product of the manufacturing sector in Indonesia, while investment did not have a significant effect on the gross domestic product of the manufacturing sector in Indonesia.